Palliative care and neurology: a path to neuropalliativism - Mariana Ribeiro Marcondes da Silveira; Daniel Neves Forte (Arquivos de Neuro-Psiquiatria)
ABSTRACT This article aims to expand the understanding of how it is possible to alleviate suffering and enable a dignified life trajectory for patients with progressive neurological diseases or with severe and permanent neurological impairment. The four most common disease trajectories described for people with chronic and progressive disease used to advance care planning, Brazilian normative ethical resolutions, evidence-based benefits of palliative care (PC), as well as particularities of PC in neurology, such as neurological symptom control, caring for existential and psychological suffering, care provider’s needs and particularities of pediatric neurologic PC are reviewed.